European company survey 2009 : flexibility profiles of European companies - Kerkhofs, Marcel; Román, Amelia; Ester, Peter; European Foundation for the Improvement of Living and Working Conditions (European Foundation for the Improvement of Living and Working Conditions, 2010)
Summary.
Keywords: yhtiöt : EU-maat; työolot : EU-maat; työaika : EU-maat; joustotyö : EU-maat; työmarkkinat : EU-maat